RADIKALISME DALAM PANDANGAN ISLAM (Analisa dalam Perspektif al Qur’an dan Hadits) - Muhammad Qomarullah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
Islam is a religion that was revealed to the Prophet Muhammad as the last prophet and messenger for a way of life of all mankind until the end of time. Understanding Islam harfiyah means